Analyzing Assessment Practices for Indigenous Students - Preston, Jane P.; Claypool, Tim R. (Frontiers in Education, 2021)
The purpose of this article is to review common assessment practices for Indigenous students. We start by presenting positionalities—our personal and professional background identities. Then we explain common terms associated with Indigeneity and Indigenous and Western worldviews. We describe the meaning of document analysis, the chosen qualitative research design, and we explicate the delimitations and limitations of the paper. The review of the literature revealed four main themes. First, assessment is subjugated by a Western worldview. Next, many linguistic assessment practices disadvantage Indigenous students, and language-specific and culture-laden standardized tests are often discriminatory. Last, there is a pervasive focus on cognitive assessment. We discuss how to improve assessment for Indigenous students. For example, school divisions and educators need quality professional development and knowledge about hands-on assessment, multiple intelligences, and Western versus Indigenous assessment inconsistencies. Within the past 20 years, assessment tactics for Indigenous students has remained, more or less, the same. We end with a short discussion addressing this point.